PRAGMATISME SEMU DEMOKRASI DAN KENDALA ACUAN PENDIDIKAN KARAKTER; FENOMENA POLITIK TRANSAKSIONAL PEMILU LEGISLATIF 2014 DI LOMBOK TIMUR - Nahdi, Khirjan (Jurnal Review Politik, 2014)
This article tries to map the political competence of legislative candidates and voters. It also attempts to formulate the simulation of the future democracy reality and formulate character education, which could be a comprehensive reference in political education. This becomes important matter for the democratic process,  which is initiated from a comprehensive political education based on plausible values and reasons. Employing qualitative-phenomenological approach, the results of analysis show that the competence of incumbent legislators are low and they are unable to convince the voters. This condition is caused by the failure of political education and the weakness of political system. The emergence of transactional motive among the voters is an effect of the failure of political education.The writer argues that this condition should be elucidated through political education which builds character and guides the voters to vote for the politicians with good morality and ability.